2006
DOI: 10.1902/jop.2006.060047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodontal Therapy During Pregnancy on Periodontal Status, Biologic Parameters, and Pregnancy Outcomes: A Pilot Study

Abstract: Results from this pilot study (67 subjects) provide further evidence supporting the potential benefits of periodontal treatment on pregnancy outcomes. Treatment was safe, improved periodontal health, and prevented periodontal disease progression. Preliminary data show a 3.8-fold reduction in the rate of preterm delivery, a decrease in periodontal pathogen load, and a decrease in both GCF IL-1beta and serum markers of IL-6 response. However, further studies will be needed to substantiate these early findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
267
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(291 citation statements)
references
References 33 publications
14
267
1
9
Order By: Relevance
“…The effect of periodontal therapy on PPD was observed to be very highly significant statistically (p<0.005) on comparison between day 0 and day 90. Similar results on PPD following periodontal therapy were observed previously by various investigators (Table 1) [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of periodontal therapy on PPD was observed to be very highly significant statistically (p<0.005) on comparison between day 0 and day 90. Similar results on PPD following periodontal therapy were observed previously by various investigators (Table 1) [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, López et al observed a significant reduction in the rate of preterm births and/or low birth weight in women that had received periodontal treatment before the 28 th gestation week when compared with women who had not received any treatment (26). Later in a pilot study by Offenbacher et al (2006), it was observed that periodontal treatment significantly reduced the incidence of preterm births, in spite of the small size of the sample (53 women) (27). Therefore, large scale longitudinal epidemiological and intervention studies are necessary to validate the causal relationship of periodontal diseases to adverse pregnancy outcomes.…”
Section: Figure 2 Possible Mechanisms Of Preterm Labormentioning
confidence: 94%
“…As an example, many studies concerning preterm delivery and periodontitis have suggested mandatory periodontal treatment among pregnant women in order to prevent undesirable effects on the foetus [3][4][5][6]. Individual types of periopathogens have been directly connected with atherosclerosis, and their presence has been noted in atheromatous plaques in blood vessels [7].…”
Section: Epidemiology Of Periodontal Diseasementioning
confidence: 99%